Potential Utilization of Palm Shells and Fibers as an Electricity Source in Bungo Regency - Elsi Alfionita Syawal; Ferdi Ashari Syawal; Illa Aryeni (Politeknik Negeri Batam, 2026)
Indonesia faces an electricity crisis due to increasing demand and heavy reliance on fossil fuels. This study examines the potential of palm oil biomass waste—shells and fibers—as fuel for a steam power plant in Bungo Regency. The methodology applies the Direct Method (Equation 1) to estimate electricity potential based on a validated boiler efficiency of 73% and actual calorific values. The results reveal that palm shells have a potential of 21,024 GWh/year, while fibers can generate 49,056 GWh/year. A key novelty of this research is the determination of specific fuel requirements: 2,3 kg/kw of shells and 2,6 kg/kw of fibers are needed to produce 1 kW of electricity. These findings provide precise empirical data for regional energy planning and demonstrate that integrating palm biomass into local grids offers a sustainable alternative to fossil fuels.